GROWTH RATES OF THE DEEP-SEA SCLERACTINIA DESMOPHYLLUM CRISTAGALLI AND ENALLOPSAMMIA ROSTRATA - Adkins J.F.; Wang S.-L.; Henderson G.M.; Mokadem F.; O'Shea S. (My University, 2004)
With uranium rich skeletons and density bands similar to their surface coral counterparts, deep-sea scleractinia are a promising archive of past climate. To improve the utility of fossil samples as monitors of deep ocean variability, we have measured 210Pb and 226Ra activities in a variety of modern specimens to constrain the range of growth rates. Mechanical and chemical cleaning of each sample are required to isolate the radionuclides trapped in the coral skeleton from surface contaminants. However, in many cases mechanically cleaned samples show the same overall growth rate as parallel transects of samples subjected to the full chemical and mechanical cleaning but with much higher overall activities. Three samples of Desmophyllum cristagalli show a range of vertical extension rates from 0.5 mm/yr to 2 mm/yr, consistent with previous estimates. A single Enallopsammia rostrata from the North Atlantic is over 100 years old. Its average radial growth rate is 0.07 mm/yr, and the clear banding in this direction is not consistent with annual periodicity. A minimum vertical extension rate of 5 mm/yr is estimated from the 210Pb data. Both of these species are found in the fossil record and, with the growth rates determined here, can record about 100 years of climate change. The growth rates will allow the reconstruction of climate at subdecadal resolution in D. cristagalli and even higher resolution in E. rostrata.